2022
DOI: 10.1186/s42836-022-00113-y
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with surgical site infections following joint replacement surgery: a narrative review

Abstract: Background Surgical site infection following joint replacement surgery is still a significant complication, resulting in repeated surgery, prolonged antibiotic therapy, extended postoperative hospital stay, periprosthetic joint infection, and increased morbidity and mortality. This review discusses the risk factors associated with surgical site infection. Related risk factors The patient-related factors include sex, age, body mass index (BMI), obes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 79 publications
1
15
1
Order By: Relevance
“…This approach limited the covariates considered as information related to patients' medications and characteristics such as alcohol and smoking habits are collected in primary care in the UK. as also previously reported [34,[38][39][40][41][42][43]. We observed a decreasing PJI risk with increasing age [34] ( Fig 2 and S1 Fig) as also found in other studies [34]; however the impact of age is controversial as an increased risk of PJI for older patients was reported [44] while other studies reported no relation [45,46].…”
Section: Plos Onesupporting
confidence: 88%
“…This approach limited the covariates considered as information related to patients' medications and characteristics such as alcohol and smoking habits are collected in primary care in the UK. as also previously reported [34,[38][39][40][41][42][43]. We observed a decreasing PJI risk with increasing age [34] ( Fig 2 and S1 Fig) as also found in other studies [34]; however the impact of age is controversial as an increased risk of PJI for older patients was reported [44] while other studies reported no relation [45,46].…”
Section: Plos Onesupporting
confidence: 88%
“…B A infection. On the other hand, studies discovered that advanced age was a protective factor, but male sex was a risk factor for surgical site infection (Baier et al 2019, Resende et al 2021, Li et al 2022. The patient in this study developed grade IV osteoarthritis, which necessitated a total knee arthroplasty.…”
Section: Case Reportmentioning
confidence: 61%
“…In addition, according to a relative report, the surgical time, the volume of bleeding, and the use of bone grafting could all increase the risk of infection. 24 , 25 , 26 Therefore, the above information associated with surgery was collected based on the medical records for THA.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the drainage fluid taken on the 3rd day, when the incision dressing was changed, was used for bacterial culture in the controls. In addition, according to a relative report, the surgical time, the volume of bleeding, and the use of bone grafting could all increase the risk of infection 24‐26 . Therefore, the above information associated with surgery was collected based on the medical records for THA.…”
Section: Methodsmentioning
confidence: 99%